Bankruptcy prediction indicators approach: A tool for measuring steinhoff’s risk - Cassim, Ronel Juliana' (Journal of Accounting and Investment, 2024)
Research aims: The objective of this article is to ascertain whether Steinhoff International Holdings could have successfully employed the Bankruptcy Prediction Indicators Approach model as an instrument for measuring business continuity risk prior to its significant share price fall in 2012.Design/Methodology/Approach: The study utilized a qualitative research design and document analysis approach to examine Steinhoff International Holdings' financial data from 2012-2021, using the Integrated Real-time Equity System (IRESS BFA McGregor) and the Bankruptcy Prediction Indicators Approach. In MS Excel, quantile values were determined by dividing the probability distribution into equal segments.Research findings: The findings of the analysis revealed that the Bankruptcy Prediction Indicators Approach was used to identify Steinhoff International Holdings' business continuity risk in 2012, demonstrating its usefulness in measuring risk and providing investigative tools for management amid COVID-19 challenges. It has been determined that ROE is the primary indicator with the highest predictive power of all the indicators.Theoretical contribution/Originality: This article adds to the body of knowledge on business continuity risk, and practitioners can use the findings to incorporate the Bankruptcy Prediction Indicators Approach into their annual reporting.Research limitation/Implication: The limitation consists of the sample from a single retail company listed on the Johannesburg Stock Exchange, and the published annual reports were the primary source of information for the analysis and measurement.